Social mobility in Polish transport within urban areas in the context of the development of sustainable transport - Motowidlak, Urszula (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
Transport is one of the most important sectors of the state’s economy. Its appropriate organization, mainly in urban areas, can effectively meet the needs of passengers. Those needs arise from a variety of reasons; however, transport is most often associated with daily access to work, school, college, offices and cultural and sporting facilities. Governments of large metropolitan centers, including Polish government, are facing enormous challenges related to provision of transport. Due to the high number of population, and hence extensive transport needs, these authorities are urged to use modern and efficient transport solutions. The development of society and the access to new technological possibilities and modern commercial solutions have influenced the development of transport in urban areas, as shown in the example of agglomeration.